Akt and its phosphorylation in nucleus accumbens mediate heroin‐seeking behavior induced by cues in rats. (22nd February 2021) - Zhu, Huaqiang; Zhuang, Dingding; Lou, Zhongze; Lai, Miaojun; Fu, Dan; Hong, Qingxiao; Liu, Huifen; Zhou, Wenhua
Abstract: Akt is initially identified as one of the downstream targets of phosphatidylinositol‐3 kinase (PI3K) and is involved in morphine reward and tolerance. However, whether phospholyration of Akt (p‐Akt) mediates heroin relapse remains unclear. Here, we aimed to explore the role of p‐Akt in the nucleus accumbens (NAc) in cue‐induced heroin‐seeking behaviors after withdrawal. First, rats were trained to self‐administer heroin for 14 days, after which we assessed heroin‐seeking behaviors induced by a context cue (CC) or by discrete conditioned cues (CS) after 1 day or 14 days of withdrawal. We found that the active responses induced by CC or CS after 14 days of withdrawal were higher than those after 1 day of withdrawal. Meanwhile, the expression of p‐Akt in the NAc was also greatest when rats were exposed to the CS after 14 days of withdrawal. Additionally, a microinjection of LY294002, an inhibitor of PI3K, into the NAc inhibited the CS‐induced heroin‐seeking behaviors after 14 days of withdrawal, paralleling the decreased levels of p‐Akt in the NAc. Finally, Akt1 or β‐arrestin 2 was downregulated via a lentiviral injection to assess the effect on heroin seeking after 14 days of withdrawal. CS‐induced heroin‐seeking behavior was inhibited by downregulation of Akt1, but not β‐arrestin 2, in the NAc. These data demonstrate that Akt phosphorylation in the NAc may play an important role in the incubation of heroin‐seeking behavior, suggesting that the PI3K/Akt pathways may be involved in the process of heroin relapse and addiction. Abstract : The heroin‐seeking behavior induced by contextual or conditioned cues incubated following withdrawal, meanwhile the expression of p‐Akt‐473 in the NAc increased parallelly. Injection of LY294002, an inhibitor of PI3K into the NAc inhibited the cues‐induced heroin‐seeking behaviors and decreased levels of p‐Akt in the NAc. Finally, only Akt1 downregulation, but not β‐arrestin 2 in the NAc reduced incubation of heroin‐seeking behavior. These findings suggest an important role for the PI3K/Akt pathways in the NAc in heroin relapse and addiction.